Peran Mediasi Kepuasan Terhadap Loyalitas dengan Basis E-Keamanan pada Pengguna E-Marketplace Indonesia - Nanang Apriliyanto; Septian Dwi Cahyo; Gilang Kharisma Putra (sekolah Tinggi Ilmu Ekonomi Dharmaputra Semarang, 2024)
Digitalization is increasing in Indonesia, this also happens in the world of shopping. the benefits gained by the e-marketplace platform are so great, 2 large companies in Indonesia have experienced trillions of rupiah in profits. but this also raises concerns in online shopping, there are many cases where data is often hacked by irresponsible people. so in this case the main study of this study is to analyze the mediation effect of customer satisfaction on user loyalty based on E-security. this study is a quantitative study with the population of this study being all Indonesian E-marketplace users. while the research sample in this study amounted to 140 respondents. the results of the study in this study in the form of e-security directly affect user satisfaction and user loyalty, besides that user satisfaction can mediate the relationship between e-security and user loyalty.